Exendin‐4‐based imaging in endogenous hyperinsulinemic hypoglycaemia cohort: A tertiary Endocrine centre experience. (6th August 2020) - Garg, Robin; Shah, Ravikumar; Tiwari, Ankita; Purandare, Nilendu; Lele, Vikram R.; Malhotra, Gaurav; Verma, Priyanka; Gosavi, Vikrant; Dalvi, Abhay; Kumar Jaiswal, Sanjeet; Patil, Virendra; Ramteke‐Jadhav, Swati; et al.
Abstract: Context: Insulinoma needs accurate preoperative localization for minimally invasive surgery. Exendin‐4‐based imaging has shown promising results. Objective: To evaluate performance parameters of exendin‐4‐based imaging in insulinoma localization and compare with other imaging modalities. Design: Retrospective cross‐sectional study. Patients: We report 14 patients with endogenous hyperinsulinemic hypoglycaemia (EHH) managed at our centre; in whom, the final diagnosis was insulinoma (n = 11), Munchausen syndrome (MS) (n = 2) and inconclusive (n = 1). Retrospective reporting of CECT, 68 Ga‐DOTATATE PET/CT and 68 Ga‐NODAGA‐exendin‐4‐PET/CT was done. With per‐lesion analysis, performance parameters were calculated for the histopathological diagnosis of insulinoma. Main Outcome Measures: True positive (TP), false positive (FP), false negative (FN), true negative (TN), sensitivity (Sn), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV) for insulinoma localization. Results: In our cohort, 12 histopathologically proven insulinoma lesions [(TP): 11 primary lesions, 1 metastasis] were detected in 11 patients, whereas two patients had MS (TN). Sn and PPV were 75% and 100%, 33.3% and 80% and 83.3% and 71.4% for CECT, 68 Ga‐DOTATATE PET/CT and 68 Ga‑NODAGA‑exendin‑4‐PET/CT, respectively. With exendin‐4‐based imaging, FP uptake in normal pancreatic tissue and FN results in the pancreatic tail lesion was seen. In one patient, TN result suggested the correct diagnosis of MS. Conclusion: 68 Ga‑NODAGA‑exendin‑4‐PET/CT has higher sensitivity than 68 Ga‐DOTATATE PET/CT and CECT for insulinoma localization. FP uptake in normal pancreas and FN result in tail lesions are limitations of currently utilized exendin‐4‐based imaging.